Nghiên cứu và phát triển chương trình đào tạo năng lực thông tin cho sinh viên trong kỷ nguyên số - Đỗ, Văn Hùng (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The article introduces and analyzes the content of information literacy and digital literacy based on the SCONUL seven pillars of information literacy and the JISC seven elements of digital literacy to show how important this information literacy is for students. It then identifies factors that directly influence the information literacy of students as well as evaluates the results of the pilot training program. Finally, it proposes a core framework for the training program on information literacy in the digital era for students.